Nuevos registros para Misiones (Argentina) de la Viudita Coluda (Muscipipra vetula) y el Chacurú Grande (Notharchus macrorhynchyus) - Schmidtuz, Carlos; Güller, Roberto; Di Santo, Hugo; Chevez, Ramón; Tahmazian, Rubén; Quinteros, Adelqui (Nuestras Aves, 2001)
Este artículo no cuenta con un resumen.